Gamma-Irradiated Bacterial Cellulose as a Three-Dimensional Scaffold for Osteogenic Differentiation of Rat Bone Marrow Stromal Cells - Farah Nurlidar; Mime Kobayashi; Ade Lestari Yunus; Rika Heryani; Muhamad Yasin Yunus; Tita Puspitasari; Darmawan Darwis (Indonesian Journal of Chemistry, 2022)
The effect of gamma-irradiation on bacterial cellulose (BC) was investigated in terms of improving its properties as scaffolds for tissue engineering. BC pellicles were exposed to 25, 50, and 75 kGy gamma-ray irradiation, and X-ray diffraction analyses showed that the crystallinity of the BC decreased as stronger irradiation accelerated BC’s degradation. Fourier transform infrared spectroscopy of the irradiated BC revealed the appearance of a new peak at 1724 cm–1, indicating the formation of a new carbonyl group due to the cleavage of glycosidic linkages of the BC. Rat bone marrow stromal cells seeded on the gamma-irradiated BC incubated in an osteogenic medium for 14 days produced calcium, a late marker for osteogenic differentiation, as shown by Alizarin Red S (ARS) staining. Gamma-irradiated BC with higher irradiation doses showed intense ARS staining indicating higher calcium deposition. These findings demonstrate the feasibility of using gamma-irradiated BC as a cytocompatible 3D scaffold for bone tissue regeneration.